Short Communication: Genetic polymorphism of registered and popularly cultivated coffee (Coffea spp.) in the Philippines using inter-simple sequence repeats markers - Arleen Panaligan; MIRIAM D. BALTAZAR; GRECEBIO JONATHAN D. ALEJANDRO (Society for Indonesian Biodiversity, 2020)
Abstract. Panaligan AC, Baltazar MD, Alejandro GJD. 2020. Short Communication: Genetic polymorphism of registered and popularly cultivated coffee (Coffea spp.) in the Philippines using inter-simple sequence repeats markers. Biodiversitas 21: 4228-4233. Three Coffea species, namely Coffea arabica, Coffea canephora and Coffea liberica have been commercially cultivated in the Philippines. Genetic variability analysis of these species is important for the conservation of genetic resources and breeding programs. Hence, this study was carried out to identify polymorphic inter-simple sequence repeats (ISSR) markers and determine the genetic variation of these three commercially cultivated coffee species. Twenty-nine DNA samples from young coffee leaves were extracted and PCR amplified. Of the 29 primers used, seven produced clear and reproducible bands. In the 54 bands produced, 51 were polymorphic. The number of bands amplified by each primer varied from 5 to 12 with an average of 7.71 bands. Polymorphism percentage ranged from 80 to 100. This is the first time that ISSR markers were used to determine the genetic variation of coffee in the Philippines. The study demonstrated the efficiency of ISSR markers to assess genetic variation in cultivated coffee species. The ISSR markers were able to differentiate the coffee germplasm at the interspecific and intraspecific levels. These results suggest the potential of ISSR markers for genetic diversity analysis of commercial coffee and varietal identification of elite varieties using DNA fingerprinting.